SPE Reservoir Characterisation and Simulation Conference and Exhibition 2015
DOI: 10.2118/175614-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Combined Low Salinity and Surfactant Flooding Effect on Oil Recovery

Abstract: A new generation improved oil recovery methods comes from combining techniques to make the overall process of oil recovery more efficient. One of the most promising methods is combined Low Salinity Surfactant (LSS) flooding. Low salinity brine injection has proven by numerous laboratory core flood experiments to give a moderate increase in oil recovery. Current research shows that this method may be further enhanced by introduction of surfactants optimized for lowsal environment by reducing the interfacial ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This implies that the hybrid LSW/LSS method is more economically efficient than the injection of surfactant at the ultralow IFT formulation. Tests performed by Araz and Kamyabi showed that precipitation of SDBS surfactant in LSW occurs when salinity concentration is above 1000 ppm [49].…”
Section: Lsw/surfactant Hybrid Eor Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the hybrid LSW/LSS method is more economically efficient than the injection of surfactant at the ultralow IFT formulation. Tests performed by Araz and Kamyabi showed that precipitation of SDBS surfactant in LSW occurs when salinity concentration is above 1000 ppm [49].…”
Section: Lsw/surfactant Hybrid Eor Techniquementioning
confidence: 99%
“…Araz and Kamyabi examined the effect of the LSW composition on the performance of core flooding by LSW/LSS in sandstones. They found that alteration in the composition of different ions in LSW and LSS affected oil recovery [49]. Therefore, it is essential to study the effect of ion composition in the LSW/LSS process in terms of oil recovery.…”
Section: Lsw/surfactant Hybrid Eor Techniquementioning
confidence: 99%
“…Tavassoli et al further elucidated that the injection of LSW prior surfactant solution recovered up to 94.4% of RF comparing to 74.5% by HSW [28]. Araz and Kamyabi [29] later debated that wettability shifted from water to neutral wet is as well favorable to enhanced RF, where up to 9.2% OOIP was additionally produced by injecting LSS after LSW.…”
Section: Introductionmentioning
confidence: 99%